EFEMP1 rs3791679 polymorphism was associated with susceptibility to glioma - Qin, Guoqiang (Int J Clin Exp Pathol, 2015)
We conducted a case-control study in a Chinese population, and investigated the association between four SNPs (rs3791679, rs1346786, rs1344733 and rs727878) in EFEMP1 and development of glioma. A case-control study was taken in the present study. The rs3791679, rs1346786, rs1344733 and rs727878 gene polymorphisms were analyzed using a polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) assay. A total of 159 patients with glioma and 364 controls were collected between July 2012 and June 2014. By unconditional logistic regression analysis, we found that individuals carrying the AA genotype and GA+AA genotype were associated with development of glioma when compared with the GG genotype, and the adjusted ORs (95% CI) were 2.13 (1.15-3.90) and 1.55 (1.04-2.32), respectively. However, we did not find that rs1346786, rs1344733 and rs727878 were significantly associated with development of glioma. Moreover, we found that the GA+AA genotype of rs3791679 was associations with a heavy increased risk of glioma in patients who have family history of cancers, and the OR (95% CI) was 6.81 (1.17-48.06). The results of our study suggested an association between the rs3791679 polymorphism and an elevated risk of glioma, especially in those with family history of glioma.